2019
DOI: 10.1016/j.midw.2019.03.021
|View full text |Cite
|
Sign up to set email alerts
|

A qualitative study of women's views on the acceptability of being asked about mental health problems at antenatal booking appointments

Abstract: ObjectiveTo explore women's views on the acceptability of being asked about mental health problems at antenatal booking. DesignQualitative study. SettingBrief semi-structured qualitative interviews were conducted with women in a private setting at a hospital, or at women's homes. Interview discussions centered around three key questions: "What was it like for you answering the questions about your mood?", "Were there any questions you found upsetting, distressing or confronting?" and "Did the midwife give you … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
9
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 18 publications
(11 citation statements)
references
References 35 publications
2
9
0
Order By: Relevance
“…Our findings are similar to those previously identified by British (Yapp et al, 2019) and Australian women in pregnancy (Rollans et al, 2013), that it is acceptable to ask about mental health but that this can cause discomfort and distress, particularly where there is a history of abuse. Women noted that the approach used by the person asking impacted on their disclosure, and that they wanted to be asked clear questions, have sufficient time to discuss issues, and receive responses which were validating and well-informed (Yapp et al, 2019). A study in the United States similarly reported that many women might not characterize their experiences as 'trauma' and prefer the use of less stigmatizing words such as 'hurt' (White et al, 2016).…”
Section: Discussionsupporting
confidence: 89%
“…Our findings are similar to those previously identified by British (Yapp et al, 2019) and Australian women in pregnancy (Rollans et al, 2013), that it is acceptable to ask about mental health but that this can cause discomfort and distress, particularly where there is a history of abuse. Women noted that the approach used by the person asking impacted on their disclosure, and that they wanted to be asked clear questions, have sufficient time to discuss issues, and receive responses which were validating and well-informed (Yapp et al, 2019). A study in the United States similarly reported that many women might not characterize their experiences as 'trauma' and prefer the use of less stigmatizing words such as 'hurt' (White et al, 2016).…”
Section: Discussionsupporting
confidence: 89%
“…Routine enquiry into mental health may require careful consideration of how to prepare the maternity environment, particularly for mental health task‐shifting initiatives in LMICs 178 . In HICs, most women welcome the opportunity to talk about mental health 179 , and there are no differences in acceptability of different modes of screening tool (e.g., paper vs. iPad) 179,180 , as long as women are given the opportunity to talk and are referred appropriately 179 . Some women, however, particularly those with mental health problems or histories of trauma, find disclosure difficult and routine enquiry less acceptable 179,180 .…”
Section: Service Deliverymentioning
confidence: 99%
“…In HICs, most women welcome the opportunity to talk about mental health 179 , and there are no differences in acceptability of different modes of screening tool (e.g., paper vs. iPad) 179,180 , as long as women are given the opportunity to talk and are referred appropriately 179 . Some women, however, particularly those with mental health problems or histories of trauma, find disclosure difficult and routine enquiry less acceptable 179,180 . In LMICs, there may be additional cultural barriers and stigma 181,182 .…”
Section: Service Deliverymentioning
confidence: 99%
“…Existing reviews have examined fathers' support needs and preferences, and their experiences as a partner of a woman who is accessing universal perinatal services and specialist perinatal mental health services (50,53,54); these have not however explicitly addressed fathers' own mental health assessment. To date there is a strong evidence base on the validity and acceptability of methods to identify maternal perinatal mental health difficulties (55)(56)(57)(58). In contrast, there is an identified lack of research on fathers' "perceptions and receptiveness" to "routine mental enquiry or screening" (pp.…”
Section: Introductionmentioning
confidence: 99%